Majority, minority, and parity: Effects of gender and group size on perceived group variability - Voci, A; Hewstone, M; Crisp, R; Rubin, M (2008)
We investigated the effects of gender and group size on perceptions of group variability, using groups of students taking different majors that varied in the proportion of men and women (female-majority, parity, and male-majority). We found that both group size and gender had consistent effects on perceived out-group variability, even when potentially confounded alternative explanations were assessed. Men showed a stronger out-group homogeneity effect than women, except when women were in the majority (Studies One and Two), and women showed no in-group homogeneity effect. There was an association between out-group homogeneity and the tendency to generate more subgroups for the in-group than out-group (Study Two), but perceived variability was not associated with familiarity, distinctiveness, perceived group size, or perceived group status. These consistent effects qualify the conclusions of prior research in important ways, and cannot be explained in terms of differences in stereotype accuracy (Study Three), or a confound between the gender majority of a major and its perceived status (Study Four). We discuss our findings in terms of theoretical explanations for gender and size effects on out-group homogeneity, and methodological considerations.